Analyzing dynamic performance of power systems over parameter space using normal forms of vector fields-part II comparison of the system structure. - Songzhe Zhu
This is part II of a two-part paper dealing with dynamic performance of power systems over the parameter space. The companion paper (part I) proposes an approach to identify unfavorable operating regions by searching for resonance and near-resonance. The results show that near-resonance among critical inertial modes and control modes may contribute to the unsatisfactory behavior of the system. In this paper, the effect of strong nonlinear modal interactions on machine states is quantified. A new index is derived to measure the relative severity of the near-resonance. The linear and nonlinear characteristics of the system are separated and correlated to the transient stability of the system
Keywords: Computer simulation; Control simulation; Critical inertial modes; Linear characteristics; Machine states; Near-resonance.; Nonlinear characteristics; Parameter space; Power system dynamic performance analysis; Resonance; Strong nonlinear modal interactions; System structure comparison; Transient stability correlation; Unfavorable operating regions identification; Vector field normal forms